A MOBILE APPLICATION FOR VIRTUAL HERITAGE AND UGC PUBLIC SHARING - L. Gongli (Beijing Qingda Transsim Technologies, Inc. 100085 Beijing, China) (Copernicus Publications, 2018)
Heritage documentation and representation is now a growing concern in the contemporary world, with unprecedentedly rapid technological development that pushes the frontier further every day. This ever growing means benefits both professionals and the general public, and the two can now be connected by this virtual bridge that channels heritage information from one end of the spectrum to the other, thus facilitating a dialogue never considered before. 4D virtual heritage with visualized tempo-spatial information can be easily shared across the continents and the story of heritage is told by a simple move of the thumb. Mobile LBS (Location-Based Service) enhances visitors' on-site experience and is readily available on the popular iOS platform. UGC (User Generated Content) on the internet provides interaction among users and managers, and brings the heritage site and the public into a live conversation. Although the above technological exploration is promising in itself, the question still remains as how it may be best implemented. The Re-yuangmingyuan program for the reconstruction and representation of an imperial garden in Beijing has made several attempts that deserve discussion, and contributes to heritage documentation and conservation in general.